A comparative analysis of LQR and fuzzy logic controller for active suspension using half car model - Hasbullah, Faried; Faris, Waleed Fekry (2010)

(untitled)
The application of the Linear Quadratic Regulator (LQR) and Fuzzy Logic Controller (FLC) in the field of active vibration isolation for a vehicle suspension system is presented and the performances of the two active controllers are compared with the passive system. The performance of the LQR controller is better than the FLC at the expense of control force. The performances of both active controllers are better than the passive system in terms of settling time. © 2010 IEEE.